Pendidikan Toleransi Beragama Bagi Generasi Milenial - Edi Sugianto (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2019)
Allah Swt. created humans from a man and woman, then making them tribe and nation, with the aim of getting to know each other (atta'aruf). Diversity is the reality of human life with a variety of cultures, ethnicities, nationalities, religions, languages, traditions, genders, etc.Recognizing diversity is a proof of human faith. However, not all accept it and understand the meaning of diversity. Therefore, tolerance education is a solution to foster mutual recognition, respect and respect for each another.Education is the right place for transformation to spread the values of tolerance; humanism, brotherhood, peace, democracy and justice. With tolerance education, there will be a millennial generation that upholds these values in the life of the nation and state.